DEVELOPMENT SRATEGY OF GOAT IN POLINGGONA DISTRICT - Agustang Agustang; Suparman Suparman; Hastuti Hastuti (Chalaza Journal of Animal Husbandry, 2016)
This research aims to identify the availability of input, effort and determine the feasibility of developing a business development of strategy of the District Polinggona. The method of this research was purposive sampling and was as many as 45 heads of household. Data collected consist of primary and secondary data. The resultof this research showed the availability of inputs in the research area.  Economically feasible to be developed because of the acceptance and the average obtained by the average total cost every goat breeder consecutively year of Rp. 10,120,888.89 and Rp. 9,733,614.43 with the value of R / C Ratio was 1.04. Obstacles encountered in the research area was the rainy season, still traditional inputs, using of care of livestock, lack of education and competition. Strategy needed to tackle the problem is to increase the production and quality of livestock as well as cooperating with the government Kolaka. The conclusion of this research were availability of the factors of production, encourage increased gains achieved so goats worthy effort in development and is supported by a development strategy that is effective in raising goats